Personal narrative of travels : to the equinoctial regions of the new continent during the years 1799-1804 - Humboldt, Alexander Von; Bonpland, Aim (NewYork : Cambridge university press, 2011)
Alexander von Humboldt's account of his monumental scientific expedition to South America and Cuba. Originally published in French between 1814 and 1825, this is the first edition in English ... This classic of scientific exploration was based on the researches of Humboldt and his companion, Aimé Bonpland, during their five-year excursion in South and Central America from 1799 to 1804. The volumes describe the voyage from Spain and the stop in the Canaries; Tobago and the first steps in South America; explorations along the Orinoco; Colombia and the area around Caracas; explorations in the northern Andes; and a visit to Cuba. "Humboldt and Bonpland traveled widely through South and Central America, studying meteorological phenomena and exploring wild and uninhabited country. At Callao, Humboldt measured the temperatures of the ocean current which came to bear his name.
Keywords: Natural history South America; South America Description and travel